Rites and passages : the beginnings of modern Jewish culture in France, 1650-1860 - Berkovitz, Jay R., 1951- (Jewish culture and contexts., 2004)
In September 1791, two years after the Revolution, French Jews were granted full rights of citizenship. Scholarship has traditionally focused on this turning point of emancipation while often overlooking much of what came before. In Rites and Passages, Jay R. Berkovitz argues that no serious treatment of Jewish emancipation can ignore the cultural history of the Jews during the ancien régime. It was during the late seventeenth and eighteenth centuries that several lasting paradigms emerged within the Jewish community-including the distinction between rural and urban communities, the formation of a strong lay leadership, heightened divisions between popular and elite religion, and the strain between local and regional identities. Each of these developments reflected the growing tension between tradition and modernity before the tumultuous events of the French Revolution.Rites and Passages emphasizes the resilience of religious tradition during periods of social and political turbulence. Viewing French Jewish history through the lens of ritual, Berkovitz describes the struggles of the French Jewish minority to maintain its cultural distinctiveness while also participating in the larger social and economic matrix. In the ancien régime, ritual systems were a formative element in the traditional worldview and served as a crucial repository of memories and values. After the Revolution, ritual signaled changes in the way Jews related to the state, French society, and French culture. In the cities especially, ritual assumed a performative function that dramatized the epoch-making changes of the day. The terms and concepts of the Jewish religious tradition thus remained central to the discourse of modernization and played a powerful role in helping French Jews interpret the diverse meanings and implications of emancipation.Introducing new and previously unused primary sources, Rites and Passages offers a fresh perspective on the dynamic relationship between tradition and modernity.